Ion-neutral chemistry at icy moons: the case of Ganymede - Beth,A; Galand,M; Jia,X; Leblanc,F (Monthly Notices of the Royal Astronomical Society, 2025)
Icy moons orbiting giant planets are often described as airless bodies though they host an exosphere where collisions between neutral species are scarce. In the case of Ganymede, the neutral composition is dominated by H2O, H2, and O2. Past observations by Galileo showed that Ganymede hosts an ionosphere and those by Juno revealed the presence of H+3 , an ion species onlystemming from ion-neutral collisions. H+3 detection suggests that ions and neutrals might still collide and be the source of new ion species on icy moons. We examine Ganymede’s ability to host a more diverse ionosphere in terms of ion composition than previously thought and predict its variety. We upgraded our test-particle code of Ganymede’s ionosphere, formerly collisionless,to include ion-neutral collisions in a probabilistic manner. The updated code is applied to three Galileo flybys of Ganymede that were investigated in the absence of chemistry. Both sets of simulations have been compared and the effect of ion-neutral chemistry has been assessed. We show that in the case of an exosphere predominantly composed of H2O, H2, and O2, theionosphere is made not only of their associated cations but also of H+3 , H3O+, and O2H+. Simulations reveal that, depending on the location, the contribution of H+3 and H3O+ to the ion composition may be significant. Strong dayside/nightside and Jovian/anti-Jovian asymmetries in the ion composition are identified. Our findings are key to interpreting Juno and future JUICEion mass spectrometer data sets.